Analysis of Oral Communication Skills of Grade IV Elementary School Students in Social Studies Learning - Oktarina, Debie; Marhayani, Dina Anika; Utama, Erdi Guna (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research aims to: 1) describe the oral communication skills of class IV students in social studies learning; 2) describe the factors that cause difficulties in students' oral communication skills. The research used is descriptive qualitative research. The subjects of this research were fourth grade students at SD Negeri 88 Singkawang. The object of this research is oral communication skills. The data analysis technique used in this research is an interactive analysis technique. Interactive analysis techniques consist of three components, namely data collection, data reduction, and drawing conclusions. The results of the research show that: 1) From the results of calculating the percentage of observations of students' oral communication skills, they are in the low oral communication skills group with a level of 34.6%, the medium oral communication skills group with a level of 50%, and the high oral communication skills group with a level of 15. 3%. From the results of the indicator percentage, there is 9.96%. The achievement of the indicator of students' oral communication skills in the indicator of being able to respect the interlocutor, while 8.00%. The lowest indicator of oral communication skills is the indicator of being able to give an opinion. 2) Most of the factors that cause difficulties in students' oral communication skills are as follows, students are not able to answer and develop their ideas to convey to the teacher or friends, students lack confidence to convey their ideas and answer questions during the learning process.